1980
DOI: 10.1007/bf00427654
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drug holidays in an animal model of tardive dyskinesia

Abstract: Intermittent haloperidol treatment in mice increased 3H-spiroperidol binding to the same degree as continual haloperidol feeding. The results do not support the concept that drug holidays can reduce the incidence of tardive dyskinesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Although several studies have examined D 2 -receptor upregulation and/or behavioral tolerance in response to an antipsychotic, none has systematically controlled for the effects of dose, duration, and in-vivo occupancyFleading to inconsistent results (Bannet et al, 1980;Carey and DeVeaugh-Geiss, 1984;Koller, 1984;Kashihara et al, 1986;Akiyama et al, 1987;Csernansky et al, 1990). Inconsistencies are possibly explained by differences in dosing, interval between last dose and D 2 -receptor measurement, and type of radioligand employed for D 2 measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have examined D 2 -receptor upregulation and/or behavioral tolerance in response to an antipsychotic, none has systematically controlled for the effects of dose, duration, and in-vivo occupancyFleading to inconsistent results (Bannet et al, 1980;Carey and DeVeaugh-Geiss, 1984;Koller, 1984;Kashihara et al, 1986;Akiyama et al, 1987;Csernansky et al, 1990). Inconsistencies are possibly explained by differences in dosing, interval between last dose and D 2 -receptor measurement, and type of radioligand employed for D 2 measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies in rats have shown that haloperidol given by continuous infusion or by depot leads to a receptor upregulation, whereas the same dose given over the same overall period but administered by daily bolus injections does not (Kashihara et al, 1986;Akiyama et al, 1987). In contrast, two other studies (Bannet et al, 1980;Koller, 1984) suggested that both sustained and intermittent haloperidol administration caused similar effects on D 2 -receptor upregulation. However, a problem with the aforementioned studies is that they used high doses of haloperidol (0.5-5 mg/kg per day) and there was no measure of drug plasma levels or drug-induced receptor D 2 -occupancy.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to the hypersensitivity developed by haloperidol given at the test carried out one week after the operation. It has been reported that a single dose of haloperidol (14) or amphetamine (15) can cause long-lasting changes in certain brain neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggest that women and elderly subjects are most often affected by this disorder (Glazer, 2000b;Jeste, 2000;Kane and Smith, 1982). Several authors have shown that factors linked to treatment, such as therapeutic class, duration (Crane and Smeets, 1974;Toenniessen et al, 1985;Turunen and Achte, 1967), dosage pattern (Gardos et al, 1977;Yassa et al, 1990), discontinuous treatment (Bannet et al, 1980;Jeste et al, 1979) and early development of extrapyramidal symptoms (Klawans et al, 1980) are risk factors in the onset of tardive dyskinesia. The use of atypical antipsychotics (Casey, 1997;Glazer, 2000b;Llorca et al, 2002) may be associated with a lower incidence of tardive dyskinesia.…”
Section: Introductionmentioning
confidence: 99%